(2x-3)+(7x+21)=90

Simple and best practice solution for (2x-3)+(7x+21)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-3)+(7x+21)=90 equation:


Simplifying
(2x + -3) + (7x + 21) = 90

Reorder the terms:
(-3 + 2x) + (7x + 21) = 90

Remove parenthesis around (-3 + 2x)
-3 + 2x + (7x + 21) = 90

Reorder the terms:
-3 + 2x + (21 + 7x) = 90

Remove parenthesis around (21 + 7x)
-3 + 2x + 21 + 7x = 90

Reorder the terms:
-3 + 21 + 2x + 7x = 90

Combine like terms: -3 + 21 = 18
18 + 2x + 7x = 90

Combine like terms: 2x + 7x = 9x
18 + 9x = 90

Solving
18 + 9x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 9x = 90 + -18

Combine like terms: 18 + -18 = 0
0 + 9x = 90 + -18
9x = 90 + -18

Combine like terms: 90 + -18 = 72
9x = 72

Divide each side by '9'.
x = 8

Simplifying
x = 8

See similar equations:

| 13x-29=155 | | -9.39-3.4d=-1.1d | | x^2-3xy+3y^2+6y=7 | | 4x+4z-2y=-1 | | 7(X-6)= | | b-7=12# | | (3X)9=24 | | (3X)9=25 | | 0=-3x^2+4x | | X+2015=Y | | 4m+5=48 | | (2x-3)=90 | | P-25=-53 | | 6x+7x-5x=-48 | | 6y=5y-8.6 | | (2x-3)=180 | | x^3+(2-i)x^2+(-4-3i)x+(1+i)=0 | | 6g=18# | | -2(y+1)=-4y+10 | | [2x-1]=3x | | 36=(x-1)2+(y-5)2 | | 7y-c=b | | -7=2(w-6)-7w | | x^2-2k(1+3k)+7(3+2k)=0 | | n+(n-8)=n+15 | | 3x-a=c | | 3.5-x=9 | | x+4y=59 | | D(y)y=2x-7 | | W=5pg^2-7pg | | 5m-2(m-1)=m-10 | | j+17=8 |

Equations solver categories